HUMAN RESOURCES CAPABILITY IMPROVEMENT STRATEGY MINING SHIP UNIT FLEET COMMAND II IN SUPPORTING THE TASK OF THE TNI NAVY - Iskandar Iskandar; Okol Sri Suharyo; Iwan Vanany (JOURNAL ASRO, 2021)
The main task of the Satran Koarmada II is to carry out the development of the strength and combat capabilities of its organic elements in the field of mine warfare in order to improve the combat capabilities of the Second Fleet Command (Koarmada II). With the condition of the Satran Koarmada II elements which are more than 30 years old and the mining technology is inadequate, it is necessary to have a strategy to increase the capacity of human resources in order to support the task of the Navy in dealing with GMTT 2030. The formulation of the problem (problem statement) of this research is how to formulate a strategy increasing the capacity of the Satran Koarmada II human resources in supporting the tasks of the Navy. The output of the SWOT and Borda analysis process in determining the strategy for improving the HR capacity of the Satran Koarmada II is a plan map or roadmap which is implemented in a strategic plan which is divided into five-year programs. The output of the SWOT and Borda analysis process in determining the strategy for improving the HR capacity of the Satran Koarmada II is a plan map or roadmap which is implemented in a strategic plan which is divided into five-year programs. The results showed that the chosen strategy was the SO Strategy which consisted of nine sub-strategies. The output of the SWOT and Borda analysis process in determining the strategy for improving the HR capacity of the Satran Koarmada II is a plan map or roadmap which is implemented in a strategic plan which is divided into five-year programs. The Borda method is used to determine the order of priority for the selected strategy which is then applied to the roadmap. The results showed that the chosen strategy was the SO Strategy which consisted of nine sub-strategies. The output of the SWOT and Borda analysis process in determining the strategy for improving the HR capacity of the Satran Koarmada II is a plan map or roadmap which is implemented in a strategic plan which is divided into five-year programs. Keywords: Improvement Strategy, Satran, SWOT, Borda, Roadmap